The antioxidative response of two tomato species with different drought tolerances as a result of drought and cadmium stress combinations - S. Ünyayar; Y. Keleş; F.Ö. Çekiç (Plant, Soil and Environment, 2005)
The effects of drought, cadmium (Cd) and drought-Cd combinations on antioxidant compounds, antioxidant enzymes and shoot growth were investigated for drought tolerant [Lycopersicon peruvianum (L.) Mill.] and sensitive of (Lycopersicon esculentum Mill. cv. Lukullus) tomato species. Drought-Cd combinations significantly decreased shoot growth in both species (P < 0.01), drought stress also decreased shoot growth in drought sensitive L. esculentum. Cd was accumulated higher in the roots of drought sensitive L. esculentum than drought tolerant L. peruvianum. The chlorophyll contents decreased in all stress treatments in L. esculentum but did not change in L. peruvianum. Carotenoid contents significantly increased in all stress treatments in both species (P < 0.01). Significant increases in the contents of carotenoids in both species under stress conditions seemed to be associated with a protective role against reactive oxygen species (ROS). Ascorbate (ASC) content decreased during drought stress while increased under Cd stress. Catalase (CAT) and glutathione reductase (GR) activities significantly increased under drought stress in L. peruvianum while decreased in L. esculentum (P < 0.001). Ascorbate peroxidase (APX) activity decreased under all stress treatments in both species. Drought and Cd stresses increased superoxide dismutase (SOD) activity in both species. The present data did not show a relation between drought tolerance and levels of antioxidative defence system that was induced from Cd. However, there is a clear relationship between Cd uptake and drought tolerance of plants.